Effects of Wellness Programs on Job Satisfaction, Stress and Absenteeism between Two Groups of Employees (Attended and Not Attended) - Dayang Nailul Munna, Abang Abdullah; Oon, Y.B. (Elsevier Ltd., 2012)
This paper presents significant relationships between employees who have attended wellness program and those who have not attended wellness program with employees’ job satisfaction, stress and absenteeism. This study was conducted at a major telecommunication company in Malaysia. 125 employees of the company were selected as respondents of this study by using simple random sampling. In addition, 63 of these respondents had attended the wellness programs whereas the other 62 had not attended the programs provided by the company. A survey questionnaire was used for data collection. The research hypotheses were tested using T-test. The findings revealed that higher job satisfaction were found in the respondents who have attended wellness program than the respondents who have not attended wellness program. The findings also showed that lower employees’ perceived stress was found among the respondents who have attended wellness program than those who have not attended wellness program; and lower employees’ absenteeism was found in the respondents who have attended wellness program than the respondents who have not attended wellness program. As a conclusion, corporate wellness program is important in promoting employees to be concerned about their health status, possibility of having sickness, and tailored treatment for their health. The challenge now is to inculcate this activity as a culture within the employees so that they would have a positive perception towards wellness programs.